If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -5n)(6 + 5n) = 0 Multiply (6 + -5n) * (6 + 5n) (6(6 + 5n) + -5n * (6 + 5n)) = 0 ((6 * 6 + 5n * 6) + -5n * (6 + 5n)) = 0 ((36 + 30n) + -5n * (6 + 5n)) = 0 (36 + 30n + (6 * -5n + 5n * -5n)) = 0 (36 + 30n + (-30n + -25n2)) = 0 Combine like terms: 30n + -30n = 0 (36 + 0 + -25n2) = 0 (36 + -25n2) = 0 Solving 36 + -25n2 = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -25n2 = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -25n2 = 0 + -36 -25n2 = 0 + -36 Combine like terms: 0 + -36 = -36 -25n2 = -36 Divide each side by '-25'. n2 = 1.44 Simplifying n2 = 1.44 Take the square root of each side: n = {-1.2, 1.2}
| 5*(2b-14)=5*b+1 | | 4b^2-8b=0 | | 6i^28=6 | | 2*m+11=4*m*11 | | 85x+1.10x=280 | | 6i^28=i | | 15x+5(.75x)=90 | | 6i^28=x | | 85x+280+1.10x=0 | | 8x^3+6x^2+x=0 | | (1b-8)(5b-2)= | | 15x+5y=90 | | (B-8)(5b-2)= | | 7(9x)+4= | | (x^2-25)= | | 3x-7=48-12x | | (6a-3)(4a-1)= | | x^2-12x+36=18 | | w-2=0 | | x^2+5x-3=3 | | 15a+8b-4a-b= | | 3-2t+1=12 | | 5t^2-7t-1=0 | | 1+5t+5=16 | | 5t^2-7+1=0 | | 15x+7=-19+2x | | 2e-12=7e+15 | | 3x+6y=20 | | 0.5(0.5x)(x)=196 | | 1-5t+5=16 | | 4z^4+2z^3-4z=0 | | 2x+2=4x-4 |